Analisis Paparan Pornografi terhadap Perilaku Seksual pada Mahasiswa Program Studi Ilmu Keperawatan di Universitas Muhammadiyah Klaten - Galang yudha W; Devi Permatasari; Sri Sat Titi Hamranani; Chori Elsera (Universitas Muhammadiyah Klaten, 2024)
Pornography is a form of visual expression in the form of images, paintings, photographs, films, videos, impressions or other communication media. The purpose of this study is to determine the relationship between pornography exposure and sexual behavior in students of the nursing study program at the University of Muhammadiyah Klaten. The method used in this study is quantitative. The data collection techniques used total sampling, data collection, and documentation techniques, and the data analysis techniques used in this study were data collection, data presentation, and conclusion drawn. The results of this study obtained the characteristics of the respondents in this study, the average age of the respondents was 18.87 years. Most of the respondents were female as many as 91 adolescents (77.8%) and male respondents amounted to 26 adolescents (22.2). Respondents who lived with their parents were 89.7%, the average of the last education of adolescent parents was 81.2% with high school/high school education, exposure to pornography in adolescents of the S1 Nursing Study Program Level 1 at the University of Muhammadiyah Klaten with the vulnerable category exposed to 43 adolescents (36.8%), exposure to light pornography as many as 6 adolescents (5.1%), mild addiction as many as 64 adolescents (54.7%), and severe addiction as many as 4 adolescents (5.4%), the number of sexual behaviors in adolescents at the University of Muhammadiyah Klaten Most of the respondents experienced sexual behavior with an unsafe category of 68 people (58.1%). The conclusion obtained in this study is that there is a relationship between pornography exposure and sexual behavior in S1 adolescents level 1 of the S1 Nursing Study Program at the University of Muhammadiyah Klaten with a p value = 0.000 and a correlation coefficient value of r = 0.931 which means that the level of closeness of the relationship between variables has a very strong relationship